+0  
 
0
38
1
avatar

(8x^3)*(-27)

Guest Jul 13, 2017
Sort: 

1+0 Answers

 #1
avatar+4060 
+1

    (8x3)   *   (-27)

 

=  (8 * x3) * (-27)

 

=  8   *  x3  *  -27

 

=  8  *  -27  *  x3

 

=  -216  *  x3

 

=  -216x3

hectictar  Jul 14, 2017

11 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details